2012
DOI: 10.1111/j.1365-2133.2011.10692.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planopilaris following hair transplantation and face-lift surgery

Abstract: Cosmetic surgical procedures, including hair transplantation and face-lift surgery, are becoming increasingly popular. However, there is very little information regarding the associated development of dermatological conditions following these procedures. Lichen planopilaris (LPP) is an uncommon inflammatory hair disorder of unknown aetiology that results in permanent alopecia and replacement of hair follicles with scar-like fibrous tissue. Frontal fibrosing alopecia (FFA), a variant of LPP, involves the fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 20 publications
3
62
0
2
Order By: Relevance
“…30 FFA has also been J AM ACAD DERMATOL VOLUME 68, NUMBER 5 described in patients following cosmetic procedures (eg, hair transplantation and face-lift surgery). 16,34 One of our patients had previous face-lift surgery and another had rhinoplasty surgery, although a temporal relationship is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…30 FFA has also been J AM ACAD DERMATOL VOLUME 68, NUMBER 5 described in patients following cosmetic procedures (eg, hair transplantation and face-lift surgery). 16,34 One of our patients had previous face-lift surgery and another had rhinoplasty surgery, although a temporal relationship is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Cases may also accidentally be discovered as new onset of LPP after hair transplantation was performed without scalp biopsies prior to the procedure. Cases of LPP after hair transplant surgery have been reported recently [4][5][6] , and although it has been suggested that LPP occurs due to the loss of immune privilege after surgery [6] , it is possible that LPP in at least some of the reported patients did not occur de novo but rather had coexisted with the MPHL prior to the surgery. In fact, if our 14 male patients who requested hair transplantation for their MPHL had not been biopsied prior to the transplantation they could have developed classic LPP afterwards.…”
Section: Discussionmentioning
confidence: 94%
“…[6] Lichen planuspilaris (LPP) like changes has been reported to occur after hair transplantation. [78] LPP is basically a histopathologic diagnosis characterized by perifollicular lymphocytic inflammation and fibrosis around the infundibular and isthmus. [910] These changes were presumed to be due to factors including koebnerization, loss of hair follicle immunoprivilege, autoimmunity, coincidence or misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%